Emergency thoracotomy: how to do it in 2026 - Adam Chesters; Michael Hughes; Erica Ley; Matthew O’Meara; Gareth Davies; Anil Hormis (Emergency Medicine Journal, 2026)
The prehospital and emergency department practice of emergency thoracotomy has evolved since Wise et al published their influential 2005 ‘how-to’ guide. Contemporary practice incorporates refined indications, clearer survival windows, improved understanding of traumatic pathophysiology and enhanced operational, human factors and safety considerations. This updated practical guide provides a modern stepwise approach to emergency thoracotomy in pre-hospital and emergency department settings. It integrates current international guideline recommendations with two decades of operational experience, offering detailed procedural steps, troubleshooting strategies and pragmatic considerations for clinicians who may rarely perform the procedure. This guide aims to support safe, timely and effective decision-making in one of the most time-critical interventions in trauma care.